Leiomyosarcoma of the sigmoid colon with multiple liver metastases and gastric cancer: a case report - Hamai Yoichi; Hihara Jun; Emi Manabu; Aoki Yoshiro; Kushitani Kei; Tanabe Kazuaki; Okada Morihito (BMC Gastroenterology, 2012)
Abstract Background Leiomyosarcoma (LMS) of the gastrointestinal tract is an extremely rare high-grade neoplasm with poor prognosis. For advanced LMS with distant metastasis, the decision as to the choice of the most appropriate therapeutic strategy, including chemotherapy and surgery, is difficult. Here, we present an unusual case of LMS of the sigmoid colon with liver metastases and gastric cancer. The survival of this patient was prolonged by a combined modality therapy involving chemotherapy and surgery. Case presentation A 66-year-old woman who had been diagnosed with advanced gastric cancer and multiple liver metastases was referred to our hospital. The initial treatment with docetaxel and S-1 considerably reduced both the gastric cancer and liver tumors; consequently we performed surgical resection. Pathological examination revealed that no viable tumor cells remained in the stomach and chemotherapy resulted in complete remission of the gastric cancer. The liver tumors were immunohistochemically diagnosed as LMS. A tumor of the sigmoid colon was subsequently discovered and the liver tumors were found to have recurred. The surgically resected sigmoid colon and liver tumors were all immunohistochemically diagnosed as LMS. These findings indicated that the multiple liver metastases arose from the LMS in the sigmoid colon, and that they were accompanied by advanced gastric cancer. We performed another surgical resection and administered chemotherapy to treat the recurring liver metastases. The patient survived for 4 years and 10 months after initial presentation at our hospital. Conclusion Colonic LMS is rare and its joint occurrence with gastric cancer is extremely unusual. Although LMS is a high-grade neoplasm, a multimodal therapeutic approach can increase patient survival time even when multiple liver metastases are present.